Monetising the dividual self : the emergence of the lifestyle blog and influencers in Malaysia - Hopkins, Julian (Anthropologist) (Anthropology of media, 2019)
"Combining theoretical and empirical discussions with shorter thick description case studies, this book offers an anthropological exploration of the emergence in Malaysia of lifestyle bloggers--precursors to current social media microcelebrities and influencers. It tracks the transformation of personal blogs, which attracted readers with spontaneous and authentic accounts of everyday life, into lifestyle blogs that generate income through advertising and foreground consumerist lifestyles. It argues that lifestyle blogs are dialogically constituted between the blogger, the readers, and the blog itself, and challenges the assumption of a unitary self by proposing that lifestyle blogs can best be understood in terms of the dividual self"--